1994
DOI: 10.1007/bf01487456
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon production concepts for dynamic annual sea ice regions

Abstract: Petroleum production from Russian seas such as the northern Timan-Pechora Basin (Pechora Sea)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For widely spaced legs, the leg factor can approach 1. In a study reported by Wang et al [44], based on model tests, the leg factor had a mean value of 0.71 and a standard deviation of 0.08. In this example a value of 0.7 will be used for four legs, 0.9 for three legs and 1 for two legs.…”
Section: Multi-leg (With Vertical Legs)mentioning
confidence: 96%
“…For widely spaced legs, the leg factor can approach 1. In a study reported by Wang et al [44], based on model tests, the leg factor had a mean value of 0.71 and a standard deviation of 0.08. In this example a value of 0.7 will be used for four legs, 0.9 for three legs and 1 for two legs.…”
Section: Multi-leg (With Vertical Legs)mentioning
confidence: 96%